Preparing for the Early eVolution Explorer: Characterizing the Photochemical Inputs and Transit Detection Efficiencies of Young Planets Using Multiwavelength Flare Observations by TESS and Swift - Ward S. Howard; Meredith A. MacGregor; Adina D. Feinstein; Laura D. Vega; Ann Marie Cody; Neal J. Turner; Valerie J. Scott; Jennifer A. Burt; Laura Venuti (The Astronomical Journal)
Ultraviolet flare emission can drive photochemistry in exoplanet atmospheres and even serve as the primary source of uncertainty in atmospheric retrievals. Additionally, flare energy budgets are not well understood due to a paucity of simultaneous observations. We present new near-UV (NUV) and optical observations of flares from three M dwarfs obtained at 20 s cadence with Swift and the Transiting Exoplanet Survey Satellite (TESS), along with a reanalysis of flares from two M dwarfs in order to explore the energy budget and timing of flares at NUV-optical wavelengths. We find a 9000 K blackbody underestimates the NUV flux by ≥2× for 54 ± 14% of flares and 14.8× for one flare. We report time lags between the bands of 0.5–6.6 minutes and develop a method to predict the qualitative flare shape and time lag to 36% ± 30% accuracy. The scatter present in optical-NUV relations is reduced by a factor of 2.0 ± 0.6 when comparing the total NUV energy with the TESS energy during the FWHM duration due to the exclusion of the T _eff ≈ 5000 K tail. We show the NUV light curve can be used to remove flares from the optical light curve and consistently detect planets with 20% smaller transits than is possible without flare detrending. Finally, we demonstrate a 10× increase in the literature number of multiwavelength flares with the Early eVolution Explorer (EVE), an astrophysics Small Explorer concept to observe young clusters with simultaneous NUV and optical bands in order to detect young planets, assess their photochemical radiation environments, and observe accretion.